Effect of Cardiopulmonary Bypass on Postoperative Nutrition of Cardiac Surgery Patients - Hosain, Suman Nazmul; Akter, Sayeda Jarina; Rasheed, Haroon; Maruf, Fazle; Ahmed, Nasiruddin (Bangladesh Medical Journal, 2009)
Introduction: Nutrition is an important factor for recovery following cardiac surgery. Most patients loose appetite and have reduced nutrition following cardiac surgery. Several factors including pain, anxiety, medications, whole body inflammatory response, Cardiopulmonary bypass (CPB) have role in postoperative anorexia and reduced nutrition. Objective: Objective of this study is to find out the role of CPB in postoperative anorexia and nutrition. Methodology: This prospective study was conducted at NICVD. 30 randomly selected adult patients who had undergone open heart surgical procedures were compared to same number of closed heart surgery patients. The daily food intake was calculated from the ICU data-sheets and calorie value obtained. The values were compared between the open and closed heart surgery patients. Results: It was noted that the open heart surgery patients took significantly less amount of food and calorie compared to the closed heart surgery patients. Conclusion: Open heart surgery is a situation where post operative nutrition plays a very significant role in patient's recovery. But unfortunately there is a tendency of the patient's taking low calorie intake for various reasons. This may have a critical role postoperatively. So adequate measures should be adopted to ensure proper postoperative nutrition following open heart surgery. DOI: 10.3329/bmj.v38i2.3574 Bangladesh Medical Journal 38(2) 2009 53-55